STUDI POLA PENGEMBANGAN JARINGAN JALAN KOTA NANGA PINOH DI KABUPATEN MELAWI - Rukmana, Didit; Erwan, Komala; Basalim, Said (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
The roadis avitaltoolthat needs tobe maintainedandenhancedfunctionstofacilitate the flow ofground transportation. Ground transportationin the city ofNangaPinoharoad networkis aland transportationinfrastructurethat really supportthegrowth and developmentof an area, duetoincreasingsocio-economic interactionsof intra and interregion. Inthis researchwilluse thetype ofsampleis purposivesamplingtechnique(purposive sampling). Thissamplingtechniqueis usedtoobtainthe dataandinformationofthe generalpublic. The resultsofthe public perception ofthe targetroad networkprovisionstatingthat theroad networkhas not beeninadequateprovisionin the City ofNangaPinohis equal to37.88%, then theopinion ofthe respondentswhoclaimed to haveinadequateprovision ofroad networksby32.32%, 19.19% is sufficient, andwasnot sufficientfor10.61%. Highest priorityin theimprovement ofthe roadnetworkprovidingservice qualityindicatorscityroad networkisthe safetyof road users, reducingthe number of accidents, androad maintenance. Kata-kata kunci: Road Network, LikertScale, NangaCityPinoh, andPriority